'A View from North of the Border': Scotland's 'Forgotten' Contribution to the History of the Prime-Time BBC1 Contemporary Single TV Play Slot. Issue 3 (2nd September 2017) - Cook, John R.
Abstract : This article surveys BBC Scotland's 'forgotten' contribution to the history of the prime-time contemporary TV play slot on BBC1, including its contributions to The Wednesday Play (BBC TV, 1964–70) and its later leading involvement with The Play on One (BBC TV, 1988–91), following the demise of the London-produced Play for Today slot (BBC TV, 1970–84). The article argues that Scotland's contribution to TV drama has been historically a rich one and that it is important to remember this today as BBC Scotland struggles to compete with BBC Wales in the wake of the latter's designation as a national 'Drama Hub'.